Fishing for the impacts of climate change in the marine sector: a case study. Issue 4 (11th November 2014) - van Putten, Ingrid; Metcalf, Sarah; Frusher, Stewart; Marshall, Nadine; Tull, Malcolm
Abstract : Purpose: – This paper aims, using a case study-based research approach, to investigate the role of climate and non-climate drivers in shaping three commercial marine sectors: fishing, aquaculture and marine tourism. Essential elements of climate change research include taking a whole of systems approach, which entails a socio-ecological perspective, and considering climate challenges alongside other challenges faced by resource users. Design/methodology/approach: – The analysis is based on information gained using in-depth semi-structured interviews in a coastal community in southeast Australia. Even though climate drivers differ, the economic sectors of this community are representative of many similar coastal communities around Australia. Findings: – Results show that at a community level, people involved in, or associated with, marine sectors are aware of climate change impacts on the marine environment. Even though many may not see it as a pressing issue, the potential effect of climate change on business profitability was recognised. Both the profitability of commercial fishing and aquaculture (oysters) was affected through mostly a downward pressure on product price, while marine tourism profitability was mainly affected through changes in the number of visitors. Research limitations/implications: – A case study approach is inherently case study-specific – although generalities from complex system representation, built on local survey respondent observation and knowledge of the combined and linked physical–biological-, social-, economic- and governance drivers. This study shows the importance of a holistic approach; yet, researchers must also consider all community sectors and cross-regional investigations to avoid future resource conflicts. Practical implications: – A number of positive impacts from climate-driven change, mainly from windfall economic benefits of geographically relocated species, were reported for commercial- and charter fishing. However, no positive impacts were reported for the aquaculture- and dive sector. In the aquaculture sector, climate drivers were of great significance in industry participation, while participation in commercial fishing was mainly driven by socio-economic factors. Social implications: – To ensure the combined marine sectors retain a viable component of coastal communities' economic focus, there is a need to understand what drives participation in the marine sector, and what the role of climate change is in this. To fully understand the ramifications of climate change in the marine environment, it is essential to understand its impacts across all marine sectors. Originality/value: – Combining the different domains with climate drivers allows for identification and assessment of targeted adaptation needs and opportunities and sets up a comprehensive approach to determine future adaptation pathways.